Contribution Describe The Use Of Edutainment Methods In The Formation Of Cooperative Character In Elementary School Students - Hartanto, Nizar; Kaltsum, Honest Ummi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to analyze the use of edutainment methods in developing cooperative character among fifth grade elementary school students, and to explore how edutainment which combines educational and entertainment elements affects students' motivation and collaborative skills. Methodology: A qualitative approach was employed, with data collected through observation, interviews, and documentation. Interviews were conducted with teachers and students to gain insights into edutainment implementation and its influence on cooperation. Observations assessed student interactions during edutainment activities, and documentation supported the findings. Results: The study found that the edutainment method provided opportunities for fifth grade students at SD Muhammadiyah 18 Surakarta to actively engage in the learning process. Its application was effective in shaping and enhancing students' cooperative character. Applications/Originality/Value: This study highlights the practical value of integrating edutainment into classroom instruction to foster not only engagement but also character development, especially cooperation. It contributes to the growing body of research on character education through interactive and enjoyable learning approaches.